Carcass Characteristics and Meat Quality of Ongole Grade Cattle and Simmental Ongole Crossbred Cattle - Ngadiyono, Nono (2014)
The experiment was conducted to study the carcass characteristics and meat quality of Ongole grade (PO) cattle and Simmental Ongole crossbred (SimPO) cattle grown in a feedlot system. Six PO cattle and six SimPO cattle with the respective initial body weight of 315.6+39.46 kg and 368.3+13.23 kg were grown for 3 months and were fed with concentrates, elephant grass, soybean hulls and cassava. At the end of the experiment all cattle were slaughtered. Meat samples used were Longissimusdorsi (LD) and Biceps femoris (BF) muscles. The variables observed were carcass characteristics, carcass components, noncarcass, meat physical quality and chemical composition. The data of carcass and non-carcass were analyzed by using the analysis of variance of independent sample t-test. The data of physical quality and chemical composition of meat were analyzed by using randomized complete block design. The results showed that there were significant differences (P<0.05) on carcass weight, carcass percentage and Longissimusdorsi area (LDA) as affected by both breeds of cattle. The slaughter weight, back fat thickness, percentage of kidney, pelvic and heart (KPH) fats, carcass components and meat-bone ratio were not different significant. The non-carcass percentage of PO and SimPO did not differ significantly. The meat physical quality (water-holding capacity, cooking loss, tenderness) were significant differences (P<0.05) between both cattle breeds, but the pH did not differ significantly. The meat chemical composition (water, protein, fat content) were significant differences (P<0.05), but the ash content did not differ significantly. It could be concluded that the carcass characteristics of PO cattle were lower than those of SimPO cattle, but carcass components and non-carcass were similar relatively. The meat of SimPO cattle had the higher fat content and was more tender than meat of PO cattle. Key Words: Carcass Characteristics, MeatQuality, OngoleGrade Cattle, Simmental Ongole, Crossbred Cattle.